Implementation of the mathematical reform in Costa Rica: a teacher training experience in the use of technology: Implementación de la reforma matemática en Costa Rica: una experiencia de capacitación docente en el uso de tecnologías - Agüero Calvo, Evelyn (2020)
The new Costa Rican math programs for elementary and high school levels approved in the month of May 2012 by the Council of Higher Education place special emphasis on the use of technology in the classroom. This derives from one of the pillars in math teaching which is based on the use of intelligent and visionary digital technologiesThe Costa Rica Institute of Technology (ITCR) Math School is socially compromised and it cannot abstain itself from contributing to society; therefore, the school developed a community extension project endorsed by the ITCR Deanship of Research and Extension. This project was created to aid the Ministry of Public Education towards the implementation of the math educational reformThe project's participants included 72 elementary school teachers coming from 40 different public schools in the Cartago and Turrialba areas. These instructors attended training sessions dealing with the use of technology in math teaching. This article shows some findings related to the experience as such as well as positive and negative aspects of the educational reform implementation process from the perspective of the participantsIt is worth mentioning that the project was conducive to the development of math student teachers from the major of Math Teaching in Technological Settings (MATEC) offered by the ITCR School of Math. These math student teachers served as aids and were very actively involved in all the training sessions. They took advantage of this process to gain experience and learn more about how to get involved in addressing the needs of different teaching contexts .